Correction to: Occurrence, Risk Factors, Prognosis and Prevention of Swimming-Induced Pulmonary Oedema: a Systematic Review - Sarah Spencer; John Dickinson; Lindsay Forbes (SpringerOpen, 2019)
The original article [1] contained a minor error in Fig. 1.